Barriers and enablers to improved access to health information for patients with low health literacy in the radiotherapy department. (October 2018) - Williams, R.; Moeller, L.; Willis, S.
Abstract: Introduction: The purpose of this article is to highlight the importance of assessing health literacy in the radiotherapy department and to discuss the challenges in practice. The paper aims to identify factors to facilitate improved access to, and understanding of, health information for patients with low health literacy. Methods: A literature search was conducted using PubMed, CINAHL, Medline and Cochrane library. Non English language studies and non-healthcare related studies were excluded. Results: The search identified 9 articles relevant to assessment of low literacy and 16 articles that address communication skills and low literacy. Four key themes were identified from the selected articles: Identifying low literacy Communication strategies Assessing Understanding Use of supportive technology Conclusion: Current health literacy screening tools as a means of identifying patients with low literacy are not suitable for use in the radiotherapy department. Patient factors such as age, socioeconomic status, and education level, as well as the use of patient's evasion techniques can indicate low literacy. To address limited literacy skills, speaking in plain English, encouraging patients to ask questions and assessing patient's understanding are important methods to promote effective communication of information in patients with low literacy skills. Highlights: Improving communication for patients with low literacy can improve compliance and health outcomes. Improved access to quality health information for patients with low literacy is essential in the radiotherapy department. Radiotherapists can change their approach to information provision in radiotherapy to improve outcomes.